Impact of obstructive sleep apnea on inpatient outcomes of COVID-19: a propensity-score matching analysis of the US Nationwide Inpatient Sample 2020 - Du, Wei; Xu, Hong; Chang, Yunqi; Feng, Biying; Wang, Qiong; Li, Weifeng (Frontiers in Medicine, 2025)
BackgroundObstructive sleep apnea (OSA) is associated with health complications, but its impact on COVID-19 outcomes is not known. This study investigated the association between OSA and outcomes of hospitalized COVID-19 patients.MethodsThe Nationwide Inpatient Sample 2020 was searched for adults hospitalized for COVID-19. The outcomes of interest were in-hospital mortality, non-routine discharge, prolonged length of stay (LOS), and complications. Patients with OSA were matched to those without OSA in a 1:4 ratio using propensity score matching (PSM) according to age, sex, and major comorbidities.ResultsAfter PSM, there were 54,900 adult COVID-19 patients consisting of 10,980 with OSA and 43,920 without OSA. The mean age was 63.2 years and 62.8% were male. Patients with OSA had higher odds of respiratory failure (adjusted OR [aOR] = 1.20, 95% confidence interval [CI]: 1.14–1.25), heart failure (aOR = 1.71, 95% CI: 1.60–1.82), and arrhythmias (aOR = 1.18, 95% CI: 1.08–1.30). Conversely, OSA was associated with lower odds of cerebrovascular accidents (CVAs) (aOR = 0.71, 95% CI: 0.62–0.81, p < 0.001), and a reduced likelihood of in-hospital mortality among patients ≥70 years old (aOR = 0.82, 95% CI: 0.75–0.89, p < 0.001) and males (aOR = 0.79, 95% CI: 0.72–0.88, p < 0.001), but not females.ConclusionOSA is associated with higher risks of respiratory failure, heart failure, and arrhythmias in patients hospitalized for COVID-19. However, patients with OSA who are ≥70 years old and those who are male are less likely to have CVAs and in-hospital mortality. These findings underscore the complex relationship between OSA and COVID-19. As the study focused on hospitalized patients, the findings may not apply to mild or asymptomatic COVID-19 cases. Future research should include community-based cohorts and prospective studies to better understand this association.